Spectacle and Spectators: Higher Education and the ‘disappearance’ of Democracy - Keet, Andre (South African Journal of Higher Education, 2016)
In the absence of deep knowledge transformation and in the format of its responses to societal challenges and state politics, higher education plays a part in positioning the state as the ‘unifying horizon for all political representation’. In South Africa, a ‘designed’ human rights state, the process by which the state becomes the ‘end of politics’ was completed in less than 20 years after the 1994 democratic elections. Higher education, along with popular images, presents the state as the ‘terminal point for political thought’ and is thus complicit in the absence of an authoritative politics outside the state. Using theoretical frames related to the ‘society of the spectacle’ and ‘political outsides’, I argue that higher education contributes to the disappearance of democracy.